Knowledge and compliance of hydroxychloroquine prophylaxis for severe acute respiratory syndrome coronavirus 2 infection among Indian health-care workers - Rudrashish Haldar; Prabhaker Mishra; Mohan Gurjar; Om Prakash Sanjeev; Vijai Datta Upadhyaya; Ankur Bhatnagar; Dharmendra Bhadauria; Vikas Agarwal (Wolters Kluwer Medknow Publications, 2022)
Objective: In the initial days of the coronavirus disease 2019 (COVID-19) pandemic, the Indian Council of Medical Research (ICMR) recommended the use of hydroxychloroquine (HCQ) as chemoprophylaxis for health-care workers (HCWs) involved in the care of COVID-19 patients. The present survey aimed to assess the knowledge and compliance of HCQ prophylaxis as per the ICMR recommendations among Indian HCWs during the first wave of the pandemic. Methods: A validated 19-item questionnaire-based survey was distributed to HCWs in our apex tertiary care institute who had completed their duties in the COVID-19 wards to assess the knowledge, attitude, and compliance of all sections of HCWs regarding the ICMR-recommended HCQ prophylaxis. Participation in the survey was voluntary, and anonymity was maintained. Data obtained from the responses were collated and analyzed. Findings: Two hundred and fourteen out of 250 HCWs completed the survey (85.6% response rate). Among 214 participants, 87.9% were below the age of 40 years. 83.2% were aware of the use of HCQ for possible prevention of COVID-19 infection, while only 24.6% took HCQ for 7 weeks as was recommended during that period. The main reasons given by 37.3% of the HCWs for not taking HCQ were their knowledge and research on HCQ, where side effects were prominent. Side effects were reported by 35% of the respondents, of which the most notable was nausea/vomiting (14%) followed by gastritis (12%). Conclusion: The poor compliance with HCQ prophylaxis by HCWs was influenced by their knowledge and research, lack of strong scientific evidence, and drug-associated adverse effects.